Interconversion and Removal of Inorganic Nitrogen Compounds via UV Irradiation - Senn, Alejandro Marcelo (2023)
Dissolved inorganic nitrogen (DIN) species are key components of the nitrogen cycle and are the main nitrogen pollutants in groundwater. This study investigated the interconversion and removal of the principal DIN compounds ((Formula presented.), (Formula presented.) and (Formula presented.)) via UV light irradiation using a medium-pressure mercury lamp. The experiments were carried out systematically at relatively low nitrogen concentrations (1.5 mM) at varying pHs in the presence and absence of oxygen to compare the reaction rates and suggest the reaction mechanisms. (Formula presented.) was fully converted into (Formula presented.) at a pH > 3 in both oxic and anoxic conditions, and the reaction was faster when the pH was increased following a first-order kinetic at pH 11 (k = 0.12 min−1, R2 = 0.9995). (Formula presented.) was partially converted into (Formula presented.) only at pH 3 and in the presence of oxygen and was stable at an alkaline pH. This interconversion of (Formula presented.) and (Formula presented.) did not yield nitrogen loss in the solution. The addition of formic acid as an electron donor led to the reduction of (Formula presented.) to (Formula presented.). Conversely, (Formula presented.) was converted into (Formula presented.), (Formula presented.) and to an unidentified subproduct in the presence of (Formula presented.) at pH 10. Finally, it was demonstrated that (Formula presented.) and (Formula presented.) react via UV irradiation with stoichiometry 1:1 at pH 10 with the total loss of nitrogen in the solution. With these results, a strategy to remove DIN compounds via UV irradiation was proposed with the eventual use of solar light.